Current perspectives on the surgical management of mandibular third molars in the United Kingdom: the need for further research. Issue 3 (April 2020) - Omran, A.; Hutchison, I.; Ridout, F.; Bose, A.; Maroni, R.; Dhanda, J.; Hammond, D.; Moynihan, C.; Ciniglio, A.; Chiu, G.
Abstract: This survey of expert opinion regarding the management of mandibular third molar (M3M) impaction and its clinical sequelae was circulated to all members of the British Association of Oral and Maxillofacial Surgeons (BAOMS). It was completed by 289 clinicians who reported treating 60 003 patients annually. Respondents included 199 (69%) specialists and 58 (20%) primary care clinicians. Most (99%) of the clinicians treated at least one M3M with complete surgical removal (CSR) annually. Only 69% performed one or more coronectomies (COR). Advocates of coronectomy reported lower rates of inferior alveolar nerve (IAN) injury, but IAN, lingual nerve, and adjacent second molar damage were rare, occurring in less than 0.5% of cases, with small differences between the COR and CSR groups. Although these differences are not statistically significant, they are likely to be clinically important. Also, the COR group would have comprised mainly high-risk teeth, while the CSR group would include many teeth at low risk of complications. This might have skewed the results. Those clinicians performing no coronectomies cited three main reasons for being low adopters of COR: the lack of irrefutable evidence to support its benefit, the increased need for a second operation, and more non-IAN complications. Although COR may prevent permanent IAN damage in high-risk cases, this paper highlights clinicians' views that there is a gap in evidence and knowledge to support COR. As a result, 47% of the clinicians surveyed recommended, and were prepared to participate in, further studies to determine the effectiveness and safety of COR.